A novel elicitor MoVcpo is necessary for the virulence of Magnaporthe oryzae and triggers rice defense responses - Nie, Yanfang; Li, Guanjun; Li, Jieling; Zhou, Xiaoshu; Zhang, Yanzhi; Shi, Qingchuan; Zhou, Xiaofan; Li, Huaping; Chen, Xiao-Lin; Li, Yunfeng (Frontiers in Plant Science, 2022)
Rice blast caused by Magnaporthe oryzae is one of the most important diseases of rice. Elicitors secreted by M. oryzae play important roles in the interaction with rice to facilitate fungal infection and disease development. In recent years, several elicitor proteins have been identified in M. oryzae, and their functions and importance are increasingly appreciated. In this study, we purified a novel elicitor-activity protein from M. oryzae, which was further identified as a vanadium chloroperoxidase (MoVcpo) by MAIDL TOF/TOF MS. The purified MoVcpo induced reactive oxygen species (ROS) accumulation in host cells, up-regulated the expression of multiple defense-related genes, thus significantly enhancing rice resistance against M. oryzae. These results suggested that MoVcpo functions as a pathogen-associated molecular pattern (PAMP) to trigger rice immunity. Furthermore, MoVcpo was highly expressed in the early stage of M. oryzae infection. Deletion of MoVcpo affected spore formation, conidia germination, cell wall integrity, and sensitivity to osmotic stress, but not fungal growth. Interestingly, compared with the wild-type, inoculation with MoVcpo deletion mutant on rice led to markedly reduced ROS accumulation, decreased expression of defense-related genes, but also lower disease severity, suggesting that MoVcpo acts as both an elicitor activating plant immune responses and a virulence factor facilitating fungal infection. These findings reveal a novel role for vanadium chloroperoxidase in fungal pathogenesis and deepen our understanding of M. oryzae-rice interactions.